2011
DOI: 10.1186/1475-2875-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial activity of Holarrhena antidysenterica and Viola canescens, plants traditionally used against malaria in the Garhwal region of north-west Himalaya

Abstract: BackgroundThe increasing number of multidrug-resistant Plasmodium strains warrants exploration of new anti-malarials. Medicinal plant research has become more important, particularly after the development of Chinese anti-malarial drug artemisnin from Artemisia annua. The present study shows evaluation of anti-malarial effects of two plants commonly used against malaria in the Garhwal region of north-west Himalaya, in order to discover the herbal-based medicine.MethodsIn vitro anti-plasmodial sensitivity of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
(29 reference statements)
0
39
0
1
Order By: Relevance
“…48) This result could provide a pharmacological basis to inhibit PRRSV replication. 27) In addition, many other plant-derived substances from TMPs such as Murraya koenigii, Erythrina caffra, Corydalis saxicola, Larrea tridentate, Holarrhena antidysenterica, and Melampyrum arvense exerted antiviral, 49,50) antibacterial, 51,52) and antiprotozoal 53,54) activities.…”
Section: Major Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…48) This result could provide a pharmacological basis to inhibit PRRSV replication. 27) In addition, many other plant-derived substances from TMPs such as Murraya koenigii, Erythrina caffra, Corydalis saxicola, Larrea tridentate, Holarrhena antidysenterica, and Melampyrum arvense exerted antiviral, 49,50) antibacterial, 51,52) and antiprotozoal 53,54) activities.…”
Section: Major Pharmacological Activitiesmentioning
confidence: 99%
“…The best classical example is that of Catharanthus roseus (Apocynaceae), used by people indigenous to southeastern Madagascar as an oral hypoglycemic agent. After laboratory research was conducted on the plant, it was found to contain more than 75 alkaloids, among which vinblastine (52) and vincristine (53) (Fig. 8) have shown high rates of success in treating childhood leukemia and Hodgkin's disease.…”
Section: Modern Ethnobotany and Pharmacol-ogically Active Constituentmentioning
confidence: 99%
“…27 Chloroform bark extract demonstrated the greatest anti-plasmodial activity, with an average IC 50 value of 5.7 mg/ml in the in vitro experiment and 70% suppression of parasitaemia in the in vivo experiment when administered at 30 mg/kg. 27 …”
Section: Anti-malarial Activitymentioning
confidence: 98%
“…1 Its stem bark has been well reported for antibacterial, antidiarrheal, anti-malarial, muscle relaxant, CNS depressant activities. [2][3][4][5][6] Seeds of this plant has potentials for free radical scavenging, anti-diabetic, hypoglycemic, antidiuretic, anti-hyperlipi-dimic and in vivo and in vitro anti-urolithic activities. [7][8][9][10][11][12] Leaves of H.…”
Section: Introductionmentioning
confidence: 99%